2018
DOI: 10.1007/s10853-017-1973-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the TiC particle size on the preferred oxidation temperature for self-healing of oxide ceramic matrix materials

Abstract: The effect of particle size on the oxidation kinetics of TiC powders is studied. Different sizes of TiC powder ranging from nanometre to submillimetre sizes are investigated. The samples are heated at different heating rates from room temperature up to 1200°C in dry synthetic air. The Kissinger method for analysis of non-isothermal oxidation is used to estimate the activation energy for oxidation of the powders and to identify the active temperature window for efficient self-healing. The master curve plotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…It is generally observed that any CTE mismatch between the particles and the matrix would lead to thermal stresses and in turn result in possible microcracking, thus potentially weakening the self-healing material. In the research on extrinsic self-healing ceramics reported in [46,47], the CTE mismatch between the healing particles and the ceramic matrix is considered as one of the important criteria for the selection of the healing agent. In contrast, for metal matrix particulate composites [48,49] the CTE mismatch between the particle and the metal matrix is found to improve the strength and toughness of the composite material owing to the induced plastic deformation of the matrix.…”
Section: Multiple Particles Simulation Setupmentioning
confidence: 99%
“…It is generally observed that any CTE mismatch between the particles and the matrix would lead to thermal stresses and in turn result in possible microcracking, thus potentially weakening the self-healing material. In the research on extrinsic self-healing ceramics reported in [46,47], the CTE mismatch between the healing particles and the ceramic matrix is considered as one of the important criteria for the selection of the healing agent. In contrast, for metal matrix particulate composites [48,49] the CTE mismatch between the particle and the metal matrix is found to improve the strength and toughness of the composite material owing to the induced plastic deformation of the matrix.…”
Section: Multiple Particles Simulation Setupmentioning
confidence: 99%
“…At 800°C the healing process required a healing time of 16 hours. 104 Boatemaa et al studied the effect of TiC particle size on the kinetics of the oxidation process including its temperature; different sizes ranging from nanometer to micrometer were used in order to study the effect of the particle size on the oxidation process as a kinetic to heal the cracks. In their study, they used a model to determine/predict the healability of the particles used in their research.…”
Section: Ceramics Thin Films and Its Composites/ Concepts And Previmentioning
confidence: 99%
“…In their study, they used a model to determine/predict the healability of the particles used in their research. 104 Shi et al studied the crack-healing behavior in ceramic-based composites through utilizing the electrochemically assisted anodization process at room temperature in 1 mol/C H 3 PO 4 electrolyte solution (galvanostatic). In this process, the composites were used as anodes and Pt as cathode, the distance between the cathode and anode is 15 mm.…”
Section: Ceramics Thin Films and Its Composites/ Concepts And Previmentioning
confidence: 99%
See 2 more Smart Citations